Post Pandemic Consumer Behavior: Conceptual Framework - Nuradli Ridzwan Shah Mohd Dali; Hanifah Abdul Hamid; Wan Rasyidah Wan Nawang; Wan Nur Fazni Wan Mohamad Nazarie (Universiti Sains Islam Malaysia, 2024)
Theories on consumer behavioral change emerged from the study of psychology and later used on consumer behaviors. Behaviorists believe that human behaviors can change from stimulus and responses based on the theories developed by Pavlov, Skinner, Thorndike, and many others. In this paper, the COVID-19 pandemic has forced many countries to take actions such as restricting people movement, providing economic stimulus to push the economy back up, and enforcing social distancing rules and alike to flatten the pandemic curve. The study envisioned that all the actions taken by the government, especially in the context of Malaysia, as stimulus that create positive and negative responses from the learning consumers. The study emulates the operant conditioning theory and proposes four different types of behavior categories that arises from the pandemic. The aim of this paper is to propose a conceptual framework of the market segmentation arising from COVID-19 pandemic. Methodology used by the study is based from the literature search and secondary data to come out with the suggested framework. The expected findings of the study are the four segments of the consumers based on their behavioral reactions post pandemic. The four segments are the back to square one, new normal, moderately new norm, and recycle consumer groups. Their preferences, needs, and wants can change the landscape of how market can be segmented apart from how business should react towards the changes in the future. Policy could be developed in terms of promoting the new norms behavior to overcome COVID-19 problems and future outbreaks as well as to ensure that Malaysia can be accommodative to the industrial revolution 4.0. Future research should be conducted to replicate the framework in different contexts and industries.